Detection of polymorphisms among Theileria parva stocks using repetitive, telomeric ribosomal DNA probes and anti-schizont monoclonal antibodies - Bishop, Richard P.; Sohanpal, B.K.; Spooner, P.R.; Dolan, T.T.; Allsopp, B.A.; Morzaria, S.P. (Cambridge University Press, 1993)
A total of 21Theileria parvastocks from 6 countries were characterized usingT. parvarepetitive and ribosomal DNA probes, aPlasmodium bergheitelomeric oligonucleotide and a panel of anti-schizont monoclonal antibodies (MAbs). Hybridization of the repetitive DNA probe to Southern blots ofEcoRI-digestedT. parvaDNA revealed 20 different restriction fragment patterns among DNA samples isolated from infections initiated using 16 parasite stocks. The panel of anti-schizont MAbs defined 8 different profiles among schizont-infected lymphoblastoid cell-cultures infected with the same 16T. parvastocks. Many stocks, which were differentiated by the repetitive DNA probe, could not be distinguished using the anti-schizont MAbs. A clonedT. parvasmall subunit ribosomal RNA (SSUrRNA) gene probe separated 17T. parvastocks into 2 groups, exhibiting either 1 or 2 restriction fragments, when hybridized toEcoRI-digestedT. parvaDNA. When hybridized toPvuII-digested DNA from 8T. parvastocks, the ribosomal probe identified 4 groups with similar restriction fragment patterns. A synthetic oligonucleotide derived from aP. bergheitelomeric sequence hybridized to 7 or 8 size-polymorphic restriction fragments in theEcoRI-digested DNA of mostT. parvastocks. The telomeric and ribosomal probes defined the same 4 groups among 8T. parvastocks as assessed by similarities in restriction fragment patterns. Based on the comparison of repetitive DNA sequences from theT. parvaUganda and Muguga stocks, a synthetic oligonucleotide was developed which distinguished the DNA of theT. parvaUganda stock from that of 4 otherT. parvastocks on a positive/negative basis.